Kyrgyz Republic : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This Report on the Observance of Standards and Codes (ROSC) provides an assessment of data dissemination practices against the IMF's General Data Dissemination System (GDDS). It also assesses the data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS) requirements, focusing on coverage, periodicity, and timeliness. It also provides an assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics.